Investigation of Multilayer Coating of EN AW 6060 - T66 using Friction Surfacing - Stephan Krall; Christian Baumann; Hemant Agiwal; Friedrich Bleicher; Frank Pfefferkorn (Journal of Machine Engineering)
The objective of this research is to investigate observable process changes during multi-layer friction surfacing of EN AW 6060 aluminum, whether for repair, remanufacturing, or new part manufacturing. In this study, friction surfacing was performed with a 10-mm-diameter rod of EN AW 6060 aluminum at spindle speeds ranging from 1000 to 7000 rpm to create up to three layers of 40-mm-long deposits on a substrate of the same alloy. The process forces and layer temperatures were observed. Post-process measurement of flash geometry, layer geometry and microhardness were conducted with the motivation to understand the impact of multi-layer depositions on performance and identifying acceptable conditions required to achieve acceptable build quality. The thickness, deposition and joining efficiency of layers in the multilayer configuration remained consistent. Friction surfacing of EN AW 6060 aluminum allowed for high deposition rates of 9 kg/hr, when compared to other metal additive technologies.